KARAKTERISTIK FISIKOKIMIA BUBUK AMPAS TOMAT-APEL HASIL PENGERINGAN PEMBUSAAN BERBANTU GELOMBANG MIKRO - Asri - Widyasanti; Nedia Cahyati Muchtarina; Sarifah - Nurjanah (Agroindustrial Technology, University of Trunojoyo Madura, 2020)
The needed for tomatoes was not comparable with the abundant of production, so tomato prices at the farm level were low. Tomato processing was needed to maintained and increased the selling value of tomatoes, it can be processed into tomato pulp powder. Tomato powder can be made by foam-mat drying method and to shortened the drying time can be done by using microwave oven. The purpose of this study was to determine the effect of the drying power used on physicochemical properties of tomato pulp powder and drying rate of foam-mat drying with microwave oven. This study conducted with laboratory experimental method with descriptive analysis. Three repetitions consisted of three treatments based on drying power used (30%, 50% and 70%). The observed parameters were total yield value, color, drying rate, drying efficiency and physicochemical properties such as color, foam density, bulk density, moisture content, ash content, water absorption index, and vitamin C content. The results showed that the average moisture content of tomato pulp was 91.73% (w.b.) and foamed tomato pulp was 90.86% (w.b.). The value of water content of tomato pulp powder ranges from 9.18% (w.b.) to 12.50% (w.b.). In this study, the best results were found in tomato pulp powder with 70% drying power without addition foaming treatment with total yield of 0.58%; 4.26 g/min drying rate; 5.86%; foam density 1 g/cm3; bulk density 0.65 g/cm3; moisture content; 9.18%; ash content 6.43%; water absorption index 19.68%; vitamin C content 154.87 mg/100g and drying efficiency was 48.27%. All of drying power used with and without foaming treatment were resulting yellow-red chromatic colour characteristic.